(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
This study explores the competitive milk tea market, focusing on Big Brew as a key player. With milk tea consumption increasing due to affordability, health benefits, and diverse flavors, competition among brands has intensified. Established in 2019, Big Brew quickly gained popularity in Metro Manila by offering a variety of beverages in a welcoming environment. However, in a monopolistic competitive market, effective marketing strategies are crucial to maintaining a strong brand presence. This study aims to enhance Big Brew’s brand image promotion using the 8Ps of the marketing mix. A mixed-method research design was employed, collecting data from fifty respondents across various branches in North Caloocan City through survey questionnaires. The findings indicate that the majority of respondents are 16-25 years old, predominantly female, and belong to lower-income brackets. Respondents generally view Big Brew’s marketing mix positively, with strong agreement across product, promotion, price, place, people, process, positioning, and performance. They particularly appreciate the product offerings and promotional efforts. A significant positive correlation was found between promotion and the marketing mix, with a p-value of 0.00001. However, concerns were raised regarding product availability, ineffective online promotion, pricing, limited store space, customer service quality, inefficient processes, and infrastructure issues. Based on the findings, recommendations include implementing a monitoring system for product supplies, diversifying promotional strategies, ensuring competitive pricing, introducing delivery services, improving customer relationships, enhancing operational efficiency, and providing parking facilities. This study highlights the significance of a well-structured marketing mix in strengthening Big Brew’s brand image. Addressing these challenges will help Big Brew solidify its competitive edge, improve customer satisfaction, and establish a stronger presence in North Caloocan City’s milk tea market.